Driving Factor for the Depth of Halal Standard Implementation in Indonesian Food Manufacturing SMEs - Tita Miawati; Junengsih Junengsih; Mala Pebriyanti; Mohamat Basori (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The halal food business is still thriving, and Indonesia has a wide-open opportunity to consolidate its position in the global halal market. SMEs are the backbone of the halal food industry. However, prior studies have been focused on halal certification and halal activities in general, while the depth of halal standard implementation has received less attention. This study intends to analyze the factors that influence the level of implementation of halal standards in halal-certified food SMEs that are participating in a business incubation program in Bogor, based on the Technology-Organization-Environment (TOE) framework. Data was collected from SMEs involved in halal-certified food manufacturing using structured questionnaires. The Partial Least Squares Structural Equation Modeling (PLS-SEM) approach was applied to assess 63 SMEs that fulfilled the study conditions. The study indicated that organizational commitment has a considerable and beneficial effect on the depth of implementation of halal standards. On the contrary, internal forces and external pressure are less effective. Possibly SMEs that have had halal certification before are at a similar level of readiness to those that are supported by a business incubation program. The study underscores the importance of organizational commitment in paving the way for higher-level adoption of halal beyond certification. The findings also give important insights to policymakers, halal facilitators, and SME development programs to further promote sustainable halal practices.